Anonymising interview data: challenges and compromise in practice. (October 2015) - Saunders, Benjamin; Kitzinger, Jenny; Kitzinger, Celia
Anonymising qualitative research data can be challenging, especially in highly sensitive contexts such as catastrophic brain injury and end-of-life decision-making. Using examples from in-depth interviews with family members of people in vegetative and minimally conscious states, this article discusses the issues we faced in trying to maximise participant anonymity alongside maintaining the integrity of our data. We discuss how we developed elaborate, context-sensitive strategies to try to preserve the richness of the interview material wherever possible while also protecting participants. This discussion of the practical and ethical details of anonymising is designed to add to the largely theoretical literature on this topic and to be of illustrative use to other researchers confronting similar dilemmas.